Eggshell derived nano‐hydroxyapatite incorporated carboxymethyl chitosan scaffold for dentine regeneration: A laboratory investigation. (23rd October 2021) - Baskar, Kaviya; Saravana Karthikeyan, Balasubramanian; Gurucharan, Ishwarya; Mahalaxmi, Sekar; Rajkumar, Gurusamy; Dhivya, Vijayakumar; Kishen, Anil
Abstract: Aim: To assess odontogenic differentiation abilities of porous biomineralizable composite scaffolds comprising eggshell derived nano‐hydroxyapatite (HAnp) and carboxymethyl chitosan (CMC) on cultured human dental pulp stem cells (hDPSCs). Methodology: Nano‐hydroxyapatite was derived from eggshells using a simple combustion method and CMC was prepared from chitosan through a chemical route. Several compositions of HAnp‐CMC (0:5, 5:0, 1:5, 2:5, 3:5, 4:5 and 1:1 w/w%) scaffolds were prepared by magnetic stirring and freeze‐drying methods. HAnp‐CMC scaffolds were characterized using high‐resolution scanning electron microscopy combined with energy‐dispersive X‐ray spectroscopy, Fourier transform infrared spectroscopy and X‐ray diffraction methods. In vitro bioactivity was determined following the interaction in simulated body fluid for 21 days. The optimized composite was then loaded onto hDPSCs to assess cell viability/proliferation, dentine sialophosphoprotein (DSPP) and vascular endothelial growth factor (VEGF) expressions using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assay, real‐time quantitative polymerase chain reaction and flow cytometry methods, respectively, following 7, 14 and 21 days. For intergroup and intragroup comparisons, Kruskal–Wallis and Friedman tests were employed, respectively, followed by appropriate post ho c test (Dunn). Significant levels were set at * p < .05 and * p < .01. Results: Synthesized hydroxyapatite (HAp) comprised crystals ranging from 20 to 50 nm (HAnp) with spherulite morphology and calcium/phosphorus (Ca/P) molar ratio of 1.67. The ultrastructure of all the scaffolds revealed a highly interconnected porous microstructure, whilst the chemical characterization displayed specific functional groups of both HAnp and CMC. In vitro bioactivity assessment confirmed the biomineralization potential of all scaffolds with an apatite‐like crystal formation on the surface. The 1:5 HAnp‐CMC revealed a favourable pore size (60–180 µm) that was suitable for cell seeding and was chosen for further experiments. Cell viability/proliferation rates of hDPSCs loaded 1:5 HAnp‐CMC at 21st day was significantly greater than that at 7th day ( p < .05). The mean relative quantification of DSPP expression by the scaffold was significantly higher ( p < .05) on day 21 (3.16) than on day 7 (1.67). Mean fluorescence intensity of the VEGF expression at day 21 (32.5) was also significantly higher ( p < .01) than at day 7 (12.54). Conclusion: hDPSCs on 1:5 HAnp‐CMC scaffolds displayed increased cell viability/proliferation and enhanced DSPP as well as VEGF expressions. The 1:5 HAnp‐CMC composite has the potential to serve as a promising scaffold for dentine regeneration.